Determinants of Foreign Direct Investment in Organization of Islamic Cooperation (OIC) Countries’ Economy - Imam Gracia Marshall; Muhammad Sena Nugraha Pamungkas; Irham Zaki; Afifah Nur Millatina; Wenny Widiantika (Falah: Jurnal Ekonomi Syariah, 2024)
The majority of organization of Islamic cooperation (OIC) countries are developing countries that need an investment to improve the welfare of the countries. This study analyzes the factor of political stability, trade openness, government performance efficiency and forms of government to foreign direct investment in the Organization of Islamic Cooperation (OIC) Countries. This study was quantitative using random effects model (REM). This research using the Data Panel to 57 member of organization of Islamic cooperation (OIC) countries with an annual distribution of data starting from 2000 – 2023. The result found that political stability, government efficiency, trade openness, and form of government are factors that have a relationship and influence on the investment climate. The results of this study contribute to enrich the discourse of political stability and government efficiency in Indonesia to attract foreign direct invesment (FDI).